EXPLORING SCIENTIFIC TRUTH THROUGH THE LOGIC OF SCIENCE IN VARIOUS PERSPECTIVES - Manggala, Kayan; Muhammad Syihabuddin; Abdullah Kafabih; Roibin (Al-Masail: Journal of Islamic Studies, 2024)
This research has several objectives, namely: (1) to know Science in the perspective of Islamic philosophy; (2) to know science in the perspective of the Qur'an; (3) to know science in the Western perspective. The method used to explore this uses a literature study method with qualitative descriptive analysis. The results of this study are three, namely (1) The characteristics of Islamic epistemology about science are belief in spiritual power, having a harmonious relationship between reason and revelation, interdependence of reason and intuition, Theocentric orientation, and associated Values Development; (2) science in the perspective of the Qur'an is illustrated in Q.S Imran : 190 and Al-Baqarah: 29; (3) Epistemology in the Western view suggests that the concept of science is based on logical principles, hypothesis generation, and verification process. There are three theories of truth, namely coherent truth theory, correspondence theory, pragmatic truth theory. In addition, there are material objects and formal objects in science. The contribution of this research describes how truth can be explained in various perspectives so that the truth becomes scientific.